2017
DOI: 10.1111/jfpp.13325
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of phenolic compounds in daylily using UHPLC-HRMSnand evaluation of drying processing method by fingerprinting and metabolomic approaches

Abstract: The flowers of daylily (Hemerocallis fulva (L.) L.) are called "Jinzhen" which are commonly used as vegetables or seasoning in East Asia. In this study, we evaluated the chemical profile changes with different processing method after harvest. Five different drying methods including solar drying, vacuum freeze drying, steam drying, and hot air drying method were investigated regarding their impact on the chemical constituents in daylily. The major phenolic compounds were tentatively characterized with ultrahigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Peak 4 was characterized as quercetin 3-arabinoside (Qu3ar) because it had fragments at m/z 433.08 ([M-H] − ) and 271 ([Y0] − ), indicating the loss of an arabinoside (150 Da) (Chen et al, 2010). A similar finding was previously reported in the daylily accession 'Baihua' (Sun et al, 2018).…”
Section: Identification Of Flavonoidssupporting
confidence: 71%
See 1 more Smart Citation
“…Peak 4 was characterized as quercetin 3-arabinoside (Qu3ar) because it had fragments at m/z 433.08 ([M-H] − ) and 271 ([Y0] − ), indicating the loss of an arabinoside (150 Da) (Chen et al, 2010). A similar finding was previously reported in the daylily accession 'Baihua' (Sun et al, 2018).…”
Section: Identification Of Flavonoidssupporting
confidence: 71%
“…Based on these principles, peak 8 was indicated as quercetin 7-glucoside (Qu7g) with λ max spectrum (band I) at ). As widely distributed flavonols in many plants (Li et al, 2009;Sarangowa et al, 2014), Qu7g and Km3g are also present in other daylily accessions (Cichewicz and Nair, 2002;Lin et al, 2011;Sun et al, 2018). Peak 4 was characterized as quercetin 3-arabinoside (Qu3ar) because it had fragments at m/z 433.08 ([M-H] − ) and 271 ([Y0] − ), indicating the loss of an arabinoside (150 Da) (Chen et al, 2010).…”
Section: Identification Of Flavonoidsmentioning
confidence: 99%
“…The specific matching information is summarized in Table 1 . In previous studies, Sun et al preliminary identified 27 phenolic compounds of flowers of daylily ( Hemerocallis fulva (L.)), indicating that rutin, kaempferol-3-O-rutinoside, 5-O-caffeoylquinic acid, and 5-O-p-coumaroylquinic acid were its major phenolic compounds [ 39 ]. The present study performed a comprehensive phytochemical scan and identified more types of plant compounds, not limited to polyphenols, which laid a firm basis for the subsequent network pharmacology analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic separation was accomplished with an Agilent InfinityLab Poroshell 120, 4.6 mm × 150 mm, 2.7 µm column were used (Agilent Infinity Lab, Wilmington, DE, USA). The detailed operation was performed according to the previous method with slight modifications, and it is presented in the Supplementary Material [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although phytochemical studies conducted on various organs of Hemerocallis have revealed the presence of many kinds of active compounds such as flavonoids [6,14,33,34], antraquinones [9,11], alkaloids [34], triterpenes [11], and caffeoylquinic acid derivatives [14,35], there is only one report about volatile oils in this genus [36].…”
Section: Resultsmentioning
confidence: 99%